Preparation method of inorganic high temperature resistant heat insulating coating and inorganic high temperature resistant heat insulating coating

By adding synthetic hydrotalcite to the phosphoric acid solution, and combining fillers such as glass fibers, the problem of reducing adhesion and heat insulation ability of inorganic high-temperature insulation coatings at extremely high temperatures is solved, and efficient thermal insulation performance is achieved.

CN119144180BActive Publication Date: 2025-03-25XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411606815.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-25
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing inorganic high-temperature heat-resistant insulating coatings have reduced adhesion and heat-insulating ability due to excessive viscosity and solid-liquid layering under extremely high temperature environments.

Method used

The modified phosphate composite bonding solution is prepared by adding synthetic hydrotalcite to the phosphoric acid solution, and its viscosity is adjusted. Combining glass fiber, glass fiber powder and calcined synthetic hydrotalcite as filler fixing agent and curing agent, uniform dispersion of fillers and normal temperature curing of coatings is achieved.

Benefits of technology

It significantly improves the adhesion and thermal insulation properties of inorganic high-temperature insulation coatings, ensuring excellent thermal insulation effect can be maintained at extreme temperatures above 600°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144180B_ABST
    Figure CN119144180B_ABST
Patent Text Reader

Abstract

The embodiment of the present disclosure provides a preparation method of an inorganic high temperature resistant thermal insulation coating and an inorganic high temperature resistant thermal insulation coating, which relates to the technical field of thermal insulation coatings, including: adding synthetic hydrotalcite to a phosphoric acid solution and stirring to generate a mixed solution, placing the mixed solution in a water bath with a condensation reflux device and heating it to a first temperature, and stirring the mixed solution at a first speed until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder; removing the condensation reflux device, and making the three-necked flask in an open state, heating it to a second temperature and continuously stirring until the solution viscosity of the modified phosphate composite binder reaches a target solution viscosity, cooling the three-necked flask to room temperature to generate a first solution; adding a filler fixative, a filler and a curing agent to the first solution in sequence, stirring at a second speed, and adding a filler to prepare an inorganic high temperature resistant thermal insulation coating. The present disclosure can improve the performance of thermal insulation coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The disclosed embodiments relate to the technical field of thermal insulation coatings, and more specifically, to a method for preparing an inorganic high-temperature resistant thermal insulation coating and an inorganic high-temperature resistant thermal insulation coating. Background Art

[0002] The collectors and pipes in the solar power generation system are often in extremely high temperature environments, especially the collector tubes and heat storage tanks, whose temperatures may exceed 500°C. Therefore, providing effective insulation and high temperature protection is crucial to improving the efficiency of the solar power generation system and extending the service life of the equipment.

[0003] Inorganic high-temperature resistant thermal insulation coatings are important materials for ensuring the stable operation of solar power generation systems because of their excellent thermal stability, ability to withstand extreme temperatures, and maintaining excellent thermal insulation effects.

[0004] In the related art, inorganic high temperature resistant heat insulating coatings are generally constructed with phosphoric acid inorganic binders and hollow glass microsphere fillers. However, due to the extremely strong acidity of phosphoric acid inorganic binders, most thickeners are difficult to thicken, which makes the coating made with phosphoric acid inorganic binders have a low viscosity; ultra-light hollow glass microsphere fillers are prone to solid-liquid stratification in inorganic binders. This phenomenon will cause the coating to peel off from the metal substrate after curing, significantly reducing the adhesion and heat insulation capacity of the coating. Summary of the invention

[0005] The purpose of the present disclosure is to provide a preparation method of an inorganic high temperature resistant thermal insulation coating and an inorganic high temperature resistant thermal insulation coating, thereby at least to a certain extent overcoming the problem of poor performance of high temperature thermal insulation coatings caused by the limitations and defects of related technologies.

[0006] According to one aspect of the present disclosure, a method for preparing an inorganic high-temperature resistant thermal insulation coating is provided, comprising: adding synthetic hydrotalcite to a phosphoric acid solution and stirring the mixture to generate a mixed solution, placing the mixed solution in a water bath with a condensation reflux device and heating it to a first temperature, and stirring the mixed solution at a first speed until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder; removing the condensation reflux device, leaving a three-necked flask in an open state, heating it to a second temperature and stirring it continuously until the solution viscosity of the modified phosphate composite binder reaches a target solution viscosity, and cooling the three-necked flask to room temperature to generate a first solution; adding a filler fixative, a filler and a curing agent to the first solution in sequence and stirring them at a second speed, and adding a filler to prepare the inorganic high-temperature resistant thermal insulation coating.

[0007] In an exemplary embodiment of the present disclosure, the molar ratio of the phosphoric acid solution to the synthetic hydrotalcite is 22-24:1.

[0008] In an exemplary embodiment of the present disclosure, the first temperature is 90°C and the second temperature is 95°C.

[0009] In an exemplary embodiment of the present disclosure, the target solution viscosity is 180-200 cps.

[0010] In an exemplary embodiment of the present disclosure, the filler fixing agent is glass fiber with a length of 2.5-3 mm; the filler is glass fiber powder with a particle size of 50-70 μm; and the filler is hollow glass microspheres.

[0011] In an exemplary embodiment of the present disclosure, the curing agent is calcined synthetic hydrotalcite, and the calcined synthetic hydrotalcite is prepared by calcining synthetic hydrotalcite in a muffle furnace.

[0012] In an exemplary embodiment of the present disclosure, the calcination temperature is 550° C. and the calcination time is 3 hours.

[0013] In an exemplary embodiment of the present disclosure, a weight ratio of the first solution to the filler fixative, the filler, the curing agent, and the filler is 88:4:4:1:10.

[0014] In an exemplary embodiment of the present disclosure, the first rotational speed is less than the second rotational speed.

[0015] According to one aspect of the present disclosure, an inorganic high temperature resistant thermal insulation coating is provided, and the inorganic high temperature resistant thermal insulation coating is prepared according to the preparation method of the inorganic high temperature resistant thermal insulation coating described in any one of the above.

[0016] In the technical solution provided in the embodiment of the present disclosure, on the one hand, a modified phosphate composite adhesive is prepared by reacting a phosphoric acid solution and a synthetic hydrotalcite, and the solution viscosity of the phosphate composite adhesive is accurately controlled to the target solution viscosity to anchor the filler, and the solution viscosity of the phosphate composite adhesive can be increased. On the other hand, by adding a fixing agent, the filler is physically supported and fixed, and the solid-liquid stratification problem of hollow glass microspheres in phosphoric acid-based inorganic adhesives is solved, and the problem of filler floating is avoided, and the uniform dispersion of the filler is achieved. On the other hand, the room temperature curing of the composite coating is achieved by a curing agent, and an inorganic high temperature resistant heat insulating coating with excellent performance is prepared. The cured coating adheres firmly to the surface of the metal substrate through the interconnected mesh structure formed, which significantly improves the adhesion and heat insulation capacity between the coating and the metal substrate.

[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0019] Figure 1 A flow chart schematically shows a method for preparing an inorganic high temperature resistant thermal insulation coating in an embodiment of the present disclosure.

[0020] Figure 2 A schematic diagram of a thermal insulation coating prepared using aluminum dihydrogen phosphate solution and hollow glass microspheres is shown schematically.

[0021] Figure 3 The schematic diagram of the heat-insulating coating prepared by using glass fiber, glass fiber powder, calcined synthetic hydrotalcite and hollow glass microspheres is shown schematically.

[0022] Figure 4 The schematic diagrams of the thermal insulation coatings prepared according to Examples 1 to 5 are schematically shown.

[0023] Figure 5 A schematic diagram of an optical microscopic image of the thermal insulation coating prepared in Example 1 is schematically shown.

[0024] Figure 6 A schematic diagram of an optical microscopic image after peeling off the thermal insulation coating prepared in Example 1 is schematically shown.

[0025] Figure 7 A schematic diagram of an optical microscopic image of the thermal insulation coating prepared in Example 3 is schematically shown.

[0026] Figure 8 A schematic diagram of an optical microscopic image after peeling off the thermal insulation coating prepared in Example 3 is schematically shown.

[0027] Fig. 9 A schematic diagram of an optical microscopic image of an aluminum substrate is schematically shown. DETAILED DESCRIPTION

[0028] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0029] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.

[0030] Inorganic high temperature resistant heat insulation coatings are an important material for ensuring the stable operation of solar power generation systems because of their excellent thermal stability, which can withstand extreme temperatures exceeding 600°C and maintain excellent heat insulation effects. This coating can be applied to the surfaces of collector pipes, heat storage tanks and other high-temperature components in solar power generation systems to reduce heat loss and improve energy efficiency. In addition, it also has good oxidation resistance, which can protect equipment from high temperature oxidation damage in harsh environments, reduce maintenance frequency, and extend the service life of equipment.

[0031] In some embodiments, inorganic high temperature resistant heat insulating coatings are generally constructed with phosphoric acid inorganic binders and hollow glass microsphere fillers with low thermal conductivity, low density, and high temperature resistance, so as to meet the requirements for high temperature environments above 500°C. However, since phosphoric acid inorganic binders are extremely acidic, most thickeners are difficult to thicken them, which makes the coating made with phosphoric acid inorganic binders have a low viscosity, and ultra-light hollow glass microsphere fillers are very prone to solid-liquid stratification in inorganic binders. This phenomenon will cause the coating to peel off from the metal substrate after curing, significantly reducing the adhesion and heat insulation capacity of the coating.

[0032] In order to solve the above technical problems, the present disclosure provides a method for preparing an inorganic high temperature resistant heat insulating coating for use in a solar power generation system or other systems. Figure 1As shown in, the preparation method of the inorganic high temperature resistant thermal insulation coating mainly includes the following steps:

[0033] In step S110, synthetic hydrotalcite is added to a phosphoric acid solution and stirred to generate a mixed solution, the mixed solution is placed in a water bath with a condensation reflux device and heated to a first temperature, and the mixed solution is stirred at a first speed until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder;

[0034] In step S120, the condensation reflux device is removed, and the three-necked flask is left in an open state, and the temperature is raised to the second temperature and stirred continuously until the solution viscosity of the modified phosphate composite binder reaches the target solution viscosity, and the three-necked flask is cooled to room temperature to generate a first solution;

[0035] In step S130, a filler fixing agent, a filler and a curing agent are sequentially added to the first solution and stirred at a second speed, and a filler is added to prepare an inorganic high temperature resistant thermal insulation coating.

[0036] Next, the preparation method of the inorganic high temperature resistant thermal insulation coating in the embodiment of the present disclosure is specifically described.

[0037] In step S110, synthetic hydrotalcite is added to a phosphoric acid solution and stirred to generate a mixed solution, the mixed solution is placed in a water bath with a condensation reflux device and heated to a first temperature, and the mixed solution is stirred at a first speed until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder.

[0038] In the disclosed embodiment, the phosphoric acid solution can be slowly added to the container, and the container can be a beaker or other container that can hold liquid. The phosphoric acid solution can be an 85% phosphoric acid solution, and the 85% phosphoric acid solution refers to a phosphoric acid solution with a mass ratio of 85%, or a phosphoric acid solution with other mass ratios. Synthetic hydrotalcite can be represented by LDHs. Among them, the molar ratio of the phosphoric acid solution to the synthetic hydrotalcite is 22 to 24:1. The stirring time for slowly adding the synthetic hydrotalcite to the phosphoric acid solution and stirring can be 10 minutes, or any suitable time.

[0039] Further, the mixed solution can be transferred to a three-necked flask and placed in a water bath to heat up until a first temperature is reached, and the first temperature can be 90°C. The water bath can be provided with a condensation reflux device, which is used to prevent the mixed solution from evaporating to ensure that the concentration and viscosity of the mixed solution remain unchanged. When the mixed solution is heated to the first temperature, stirring can be continued at a first speed until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder. The first temperature can be a temperature at which the synthetic hydrotalcite can be completely dissolved, for example, it can be 90°C. The first speed can be 800 r / min, or it can be other suitable speeds, which are not specifically limited here.

[0040] In some embodiments, 85% phosphoric acid solution can be added to a beaker, and then synthetic hydrotalcite (LDHs) can be slowly added under continuous stirring, and stirred for 10 minutes to obtain a mixed solution. The mixed solution is then transferred to a three-necked flask and placed in a water bath with a condensation reflux device, heated to a first temperature of 90° C., and continuously stirred at a first speed of 800 r / min until the synthetic hydrotalcite is completely dissolved, so as to generate a modified phosphate composite binder.

[0041] In step S120, the condensation reflux device is removed, and the three-necked flask is left in an open state, and the temperature is raised to the second temperature for continuous stirring until the solution viscosity of the modified phosphate composite binder reaches the target solution viscosity, and the three-necked flask is cooled to room temperature to generate a first solution.

[0042] In the disclosed embodiment, the condensation reflux device in the water bath can be removed, and the three-necked flask is in an open state, so that the water of the modified phosphate composite binder liquid evaporates, thereby adjusting the solution viscosity of the modified phosphate composite binder liquid. Further, the modified phosphate composite binder liquid in the three-necked flask can be heated to a second temperature by water bath heating. The second temperature can be higher than the first temperature, and the second temperature can cause the water to evaporate quickly. For example, the second temperature can be 95°C. After heating to the second temperature, continuous stirring can be performed until the solution viscosity of the modified phosphate composite binder liquid reaches the target solution viscosity and the stirring is stopped. The target solution viscosity can be 180~200cps. The target solution concentration can be determined according to the state of the filler. Exemplarily, when the state of the filler is that the filler does not float and does not affect the brushing construction, the target solution viscosity can be determined.

[0043] It should be noted that, during the process of heating to the second temperature and continuously stirring, the solution viscosity of the modified phosphate composite binder can be tested at intervals of a preset time. If the solution viscosity reaches the target solution viscosity, stirring can be stopped; if the solution viscosity does not reach the target solution viscosity, stirring can be continued until the solution viscosity reaches the target solution viscosity. The preset time can be 20 minutes or 10 minutes, which can be determined according to actual needs.

[0044] After stopping stirring, the three-necked flask can be placed in cold water to cool the modified phosphate composite binder liquid in the three-necked flask until it reaches room temperature, and the solution obtained by cooling to room temperature is used as the first solution.

[0045] In step S130, a filler fixing agent, a filler and a curing agent are sequentially added to the first solution and stirred at a second speed, and a filler is added to prepare an inorganic high temperature resistant thermal insulation coating.

[0046] In the disclosed embodiment, the filler fixing agent may be glass fiber with a length of 2.5 to 3 mm; the filler is glass fiber powder, and the particle size of the filler may be 50 to 70 μm. The curing agent is calcined synthetic hydrotalcite, i.e., calcined LDHs. The calcined synthetic hydrotalcite is obtained by calcining the synthetic hydrotalcite in a muffle furnace. The calcination temperature may be 550°C, and the calcination time may be 3 hours. In addition, the calcination temperature and calcination time may be determined according to actual needs. The filler may be hollow glass microspheres. In some embodiments, the weight ratio of the first solution to the filler fixing agent, the filler, the curing agent, and the filler may be 88:4:4:1:10.

[0047] The second speed may be higher than the first speed, and the second speed may be, for example, 1800 r / min, or any value greater than the first speed. The stirring time at the second speed may be 20 minutes, or any suitable length of time, which is not specifically limited herein.

[0048] In some embodiments, a filler fixative, a filler and a curing agent may be sequentially added to the first solution and stirred for 20 minutes at a second stirring speed of 1800 r / min. The filler may be further slowly added and stirred for 30 minutes to obtain an inorganic high temperature resistant thermal insulation coating, wherein the inorganic high temperature resistant thermal insulation coating may be a room temperature curing inorganic high temperature resistant thermal insulation coating.

[0049] Next, the preparation method of the inorganic high temperature resistant thermal insulation coating provided by the present disclosure is described in detail with reference to the embodiments.

[0050] In some embodiments, a thermal insulation coating can be prepared based on aluminum dihydrogen phosphate solution and hollow glass microspheres, and its preparation method mainly includes the following steps: take 22 g of aluminum dihydrogen phosphate solution and place it in a beaker, add 2.5 g of hollow glass microspheres at a stirring speed of 1800 r / min, and continue stirring for 30 minutes to obtain the thermal insulation coating.

[0051] In other embodiments, a thermal insulation coating can be prepared based on glass fiber, glass fiber powder, calcined synthetic hydrotalcite, and hollow glass microspheres. The specific preparation process includes: taking 22 g of aluminum dihydrogen phosphate solution and placing it in a beaker, adding 1 g of glass fiber, 1 g of glass fiber powder, and 0.25 g of calcined synthetic hydrotalcite in sequence at a stirring speed of 1800 r / min, stirring for 20 minutes, and then slowly adding 2.5 g of hollow glass microspheres, and continuing to stir for 30 minutes to obtain the thermal insulation coating.

[0052] When preparing an inorganic high temperature resistant heat insulating coating according to the preparation method in the embodiment of the present disclosure, one or more of the molar ratio of the phosphoric acid solution and the synthetic hydrotalcite, the target solution viscosity, the weight of the glass fiber, the weight of the glass fiber powder, the weight of the calcined synthetic hydrotalcite, and the weight of the hollow glass microspheres can be adjusted. In addition, the stirring time can also be adjusted. However, the weight ratio of the first solution, the glass fiber, the glass fiber powder, the calcined synthetic hydrotalcite, and the hollow glass microspheres remains unchanged.

[0053] Example 1

[0054] The preparation method of the inorganic high temperature resistant thermal insulation coating mainly comprises the following steps:

[0055] Step 1: Add 127.3 g of 85% phosphoric acid solution into a beaker, where 85% refers to the mass ratio. Then slowly add 30.2 g of synthetic hydrotalcite under constant stirring, and stir for 10 minutes to obtain a mixed solution; then transfer the mixed solution to a three-necked flask and place it in a water bath with a condensation reflux device, heat it to a first temperature of 90°C, and continue stirring at a first speed of 800 r / min until the synthetic hydrotalcite is completely dissolved to generate a modified phosphate composite binder.

[0056] Step 2: Remove the condensation reflux device in the water bath, and keep the three-necked flask open, raise the temperature to the second temperature of 95°C and continue stirring, use a rotational viscometer to test the solution viscosity every 20 minutes, and stop stirring when the solution viscosity of the modified phosphate composite adhesive is the target solution viscosity of 180-190 cps. After stopping stirring, move the three-necked flask to cold water to cool down, and mark the resulting solution as the first solution after it cools to room temperature.

[0057] Step 3: Take the first solution and place it in a beaker, for example, take 22g of the first solution. Stir at a second speed of 1800r / min, add 1g of glass fiber, 1g of glass fiber powder and 0.25g of calcined synthetic hydrotalcite in sequence, stir for 20 minutes, then slowly add 2.5g of hollow glass microspheres, continue stirring for 30 minutes, and prepare a room temperature curing inorganic high temperature resistant thermal insulation coating.

[0058] Example 2

[0059] Step 1: Add 132.2 g of 85% phosphoric acid solution to a beaker, where 85% refers to the mass ratio. Then slowly add 30.2 g of synthetic hydrotalcite under constant stirring, and stir for 10 minutes to obtain a mixed solution. Transfer the mixed solution to a three-necked flask and place it in a water bath with a condensation reflux device, heat it to a first temperature of 90°C, and continue stirring at a first speed of 800 r / min until the synthetic hydrotalcite is completely dissolved to form a modified phosphate composite binder.

[0060] Step 2: Remove the condensation reflux device and leave the three-necked flask in an open state, heat to a second temperature of 95°C and continue stirring, use a rotational viscometer to test the solution viscosity of the modified phosphate composite adhesive solution once every 20 minutes, and stop stirring when the solution viscosity of the modified phosphate composite adhesive solution reaches the target solution viscosity of 190-200 cps. After stopping stirring, quickly move the three-necked flask to cold water to cool down, and mark the resulting solution as the first solution after it reaches room temperature.

[0061] Step 3: Take the first solution and place it in a beaker, for example, take 44g of the first solution, stir at a second speed of 1800r / min, add 2g of glass fiber, 2g of glass fiber powder and 0.5g of calcined synthetic hydrotalcite to the first solution in sequence, stir for 20 minutes, then slowly add 5g of hollow glass microspheres, and continue stirring for 30 minutes to obtain a room temperature curing inorganic high temperature resistant thermal insulation coating.

[0062] Example 3

[0063] Step 1: Add 137.8g of 85% phosphoric acid solution to a beaker, where 85% refers to the mass ratio. Then slowly add 30.2g of synthetic hydrotalcite under constant stirring, and stir the reaction for 10 minutes to obtain a mixed solution. Then transfer the mixed solution to a three-necked flask and place it in a water bath with a condensation reflux device, heat it to a first temperature of 90°C, and continue stirring at a first speed of 800r / min until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder.

[0064] Step 2: Remove the condensation reflux device, and keep the three-necked flask open, raise the temperature to the second temperature of 95°C and continue stirring, use a rotational viscometer to test the solution viscosity every 20 minutes, and stop stirring when the solution viscosity of the modified phosphate composite binder reaches the target solution viscosity of 180-190 cps. After stopping stirring, quickly move the three-necked flask to cold water to cool down, and mark the resulting solution as the first solution after it cools to room temperature.

[0065] Step 3: Take 22 g of the first solution and place it in a beaker, stir at the second speed of 1800 r / min, and add 1 g of glass fiber, 1 g of glass fiber powder and 0.25 g of calcined synthetic hydrotalcite in turn, stir for 20 minutes, then slowly add 2.5 g of hollow glass microspheres, and continue stirring for 30 minutes to obtain a room temperature curing inorganic high temperature resistant thermal insulation coating.

[0066] Example 4

[0067] Step 1: Add 127.3 g of 85% phosphoric acid solution to a beaker, where 85% refers to the mass ratio. Then slowly add 30.2 g of LDHs under constant stirring, and stir to react for 10 minutes to obtain a mixed solution. Then transfer the mixed solution to a three-necked flask and place it in a water bath with a condensation reflux device, heat it to a first temperature of 90°C, and continue stirring at a first speed of 800 r / min until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder.

[0068] Step 2: Remove the condensation reflux device, and keep the three-necked flask in an open state, heat it to a second temperature of 95°C and continue stirring, and use a rotational viscometer to test the solution viscosity of the modified phosphate composite adhesive solution once every 20 minutes until the solution viscosity of the modified phosphate composite adhesive solution reaches the target solution viscosity of 180-190 cps, then stop stirring. After stopping stirring, quickly move the three-necked flask to cold water to cool it down, and mark the resulting solution as the first solution after it cools to room temperature.

[0069] Step 3: Take 44 g of the first solution and place it in a beaker, stir at a second speed of 1800 r / min, and add 2 g of glass fiber, 2 g of glass fiber powder and 0.5 g of calcined synthetic hydrotalcite to the first solution in sequence, stir for 20 minutes, and then slowly add 5 g of hollow glass microspheres, and continue stirring for 30 minutes to obtain a room temperature curing inorganic high temperature resistant thermal insulation coating.

[0070] Example 5

[0071] Step 1: Add 137.8 g of 85% phosphoric acid solution into a beaker, where 85% refers to the mass ratio. Then slowly add 30.2 g of synthetic hydrotalcite under constant stirring, stir and react for 10 minutes, then transfer the mixed solution to a three-necked flask and place it in a water bath with a condensation reflux device, heat it to a first temperature of 90°C, and continue stirring at a first speed of 800 r / min until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder.

[0072] Step 2: Remove the condensation reflux device, so that the three-necked flask is in an open state, heat up to the second temperature of 95°C and continue stirring, use a rotational viscometer to test the solution viscosity of the modified phosphate composite adhesive solution once every 20 minutes, and stop stirring when the solution viscosity of the modified phosphate composite adhesive solution reaches the target solution viscosity of 190-200 cps. After stopping stirring, quickly move the three-necked flask to cold water to cool down, and mark the resulting solution as the first solution after it cools to room temperature.

[0073] Step 3: Take 22 g of the first solution and place it in a beaker, stir at the second speed of 1800 r / min, and add 1 g of glass fiber, 1 g of glass fiber powder and 0.25 g of calcined synthetic hydrotalcite in turn, stir for 20 minutes, then slowly add 2.5 g of hollow glass microspheres, and continue stirring for 30 minutes to obtain a room temperature curing inorganic high temperature resistant thermal insulation coating.

[0074] Will Figure 2 , Figure 3 Respectively Figure 4 By comparing the thermal insulation coating prepared in Figure 2 The thermal insulation coating prepared based on aluminum dihydrogen phosphate solution and hollow glass microspheres showed solid-liquid stratification after standing for 30 minutes. Figure 3 The thermal insulation coatings prepared with glass fiber, glass fiber powder, calcined synthetic hydrotalcite and hollow glass microspheres also showed different degrees of solid-liquid stratification after standing for 30 minutes. Figure 4 The heat-insulating coating prepared in Example 1 shown in Figure (a) Figure 4 The heat-insulating coating prepared in Example 2 shown in the middle figure (b) Figure 4 The heat-insulating coating prepared in Example 3 shown in the middle figure (c) Figure 4 The heat-insulating coating prepared in Example 4 shown in the middle figure (d) Figure 4 The heat-insulating coating prepared in Example 5 shown in the middle figure (e) showed no solid-liquid separation after standing for 30 minutes. Therefore, the preparation method of the inorganic high-temperature resistant heat-insulating coating proposed in the embodiment of the present disclosure achieves uniform dispersion of hollow glass microspheres in the inorganic coating. Figure 2 The stratification degree of the thermal insulation coating prepared by using aluminum dihydrogen phosphate solution and hollow glass microspheres is much greater than Figure 3 The degree of stratification of the stratification phenomenon of the thermal insulation coating prepared according to glass fiber, glass fiber powder, calcined synthetic hydrotalcite, and hollow glass microspheres. It can be seen that the solid-liquid stratification phenomenon of hollow glass microspheres in inorganic coatings can be effectively alleviated after adding glass fiber, glass fiber powder, and calcined synthetic hydrotalcite. Based on this, in the embodiments of the present disclosure, the thermal insulation coating is prepared by adding glass fiber, glass fiber powder, and calcined LDHs filler to the inorganic binder, which can effectively alleviate the solid-liquid stratification phenomenon of hollow glass microspheres in inorganic coatings.

[0075] refer to Figure 5 as well as Figure 7 It can be seen that the room temperature curing inorganic high temperature resistant thermal insulation coatings prepared according to Example 1 and Example 3 have a complete, uniform and dense surface.

[0076] refer to Figure 6 as well as Figure 8 It can be seen that after the inorganic high temperature resistant thermal insulation coatings prepared according to Example 1 and Example 3 are peeled off, the thermal insulation coatings are Fig. 9 The surface of the aluminum substrate shown in the figure presents an interconnected mesh structure, which can fasten the inorganic high temperature resistant thermal insulation coating to the surface of a metal substrate such as an aluminum substrate, thereby enhancing the adhesion between the inorganic high temperature resistant thermal insulation coating and the metal substrate.

[0077] To summarize, in the embodiments of the present invention, a modified phosphate composite binder is prepared, and by adjusting the solution viscosity of the modified phosphate composite binder and adding long-diameter glass fibers and glass fiber powder, the problem of floating hollow glass microspheres is avoided, thereby achieving uniform dispersion of hollow glass microspheres in the inorganic coating; an inorganic high-temperature resistant thermal insulation coating that cures at room temperature is obtained by adding calcined synthetic hydrotalcite, and the cured thermal insulation coating is uniform and dense, and the interconnected network structure formed enables the coating to firmly adhere to the surface of the metal substrate, significantly improving the adhesion between the thermal insulation coating and the metal substrate, and improving the thermal insulation performance of the thermal insulation coating.

[0078] In the embodiment of the present disclosure, there is also provided an inorganic high temperature resistant thermal insulation coating prepared according to the method of step S110 to step S130. By adjusting the solution viscosity of the modified phosphate composite binder and adding long diameter glass fibers, the uniform dispersion of hollow glass microspheres in the inorganic coating is achieved; an inorganic high temperature resistant thermal insulation coating with excellent performance is prepared by phosphoric acid solution, synthetic hydrotalcite, glass fiber, glass fiber powder, calcined synthetic hydrotalcite, and hollow glass microspheres. The cured thermal insulation coating forms an interconnected mesh structure so that the thermal insulation coating adheres firmly to the surface of the metal substrate, significantly improving the adhesion between the thermal insulation coating and the metal substrate.

[0079] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0080] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

[0081] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing an inorganic high temperature resistant heat insulating coating, characterized in that: include: Adding synthetic hydrotalcite to a phosphoric acid solution and stirring to generate a mixed solution, transferring the mixed solution to a three-necked flask and placing it in a water bath with a condensation reflux device to heat it to a first temperature, and stirring the mixed solution at a first speed until the synthetic hydrotalcite is completely dissolved to obtain a modified phosphate composite binder; The molar ratio of the phosphoric acid solution to the synthetic hydrotalcite is 26-28:1; The condensation reflux device is removed, and the three-necked flask is left in an open state to adjust the solution viscosity of the modified phosphate composite binder solution, the temperature is raised to the second temperature and the solution is continuously stirred until the solution viscosity of the modified phosphate composite binder solution reaches the target solution viscosity, and the three-necked flask is quickly placed in cold water to cool to room temperature to generate a first solution; The target solution viscosity is 180-200 cps; A filler fixative, a filler and a curing agent are sequentially added to the first solution and stirred at a second speed, and hollow glass microspheres are added to prepare an inorganic high-temperature resistant thermal insulation coating; wherein the weight ratio of the first solution to the filler fixative, the filler, the curing agent and the hollow glass microspheres is 88:4:4:1:10; and the filler fixative is glass fiber.

2. The method for preparing the inorganic high temperature resistant heat insulating coating according to claim 1, characterized in that: The first temperature is 90°C and the second temperature is 95°C.

3. The method for preparing the inorganic high temperature resistant heat insulating coating according to claim 1, characterized in that: The length of the filler fixing agent is 2.5-3 mm; the filler is glass fiber powder with a particle size of 50-70 μm.

4. The method for preparing the inorganic high temperature resistant heat insulating coating according to claim 1, characterized in that: The curing agent is calcined synthetic hydrotalcite, and the calcined synthetic hydrotalcite is prepared by placing synthetic hydrotalcite in a muffle furnace for calcination.

5. The method for preparing the inorganic high temperature resistant heat insulating coating according to claim 4, characterized in that: The calcination temperature is 550° C. and the calcination time is 3 hours.

6. The method for preparing the inorganic high temperature resistant heat insulating coating according to claim 1, characterized in that: The first rotation speed is lower than the second rotation speed.

7. An inorganic high temperature resistant heat insulating coating, characterized in that: The inorganic high temperature resistant heat insulation is prepared according to the preparation method of the inorganic high temperature resistant heat insulation according to any one of claims 1-6.

Citation Information

Patent Citations

  • Normal-temperature curing phosphate coating and preparation method thereof

    CN118620426A

  • Composite inorganic flame retardant and its preparation method

    CN1837329A